PANORAMA DO DESEMPENHO GEOMÉTRICO DE EDIFÍCIOS RESIDENCIAIS DA GLEBA PALHANO EM LONDRINA-PR - Prestes, Faria Juliana; Gregorio, Paoliello (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research presents an overview of the geometric efficiency of multifamily residential architectural projects executed at Gleba Palhano in Londrina. The buildings selected to compose the sample were the highest in the area in question, all of which are part of the same zoning. To carry out this objective, we consulted the building projects already approved in the city hall and calculated the indices of compactness, percentage of the circulation area in relation to the area of the pavement type and percentage of the private area in the global area of the buildings. The results showed that in general there is a reasonable quality and geometric efficiency in the building plans studied, but that the circulation areas in the type pavements are more optimized than the perimeters in relation to the built area. Thus, there is still a good margin for possible cost reductions for future ventures. In addition, it was found that the requirement for municipal legislation to offer a large leisure area contributed to the Ppg index (percentage of the private area in relation to the global area) being classified as "good" for all buildings.